1971
DOI: 10.1159/000121990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adrenalectomy and Cortisol on the <i>in vivo</i> Rate of Incorporation of Phenylalanine-<sup>14</sup>C into Rat Corticotropin

Abstract: A method has been developed for studying the rate of in vivo ACTH synthesis by measuring the incorporation of phenylalanine-14C into ACTH in the rat. At 1 h after the intra-peritoneal injection of labeled amino acid the anterior pituitary was obtained and ACTH was extracted with hot glacial acetic acid, precipitated with ether, and adsorbed onto oxidized cellulose. The ACTH fraction was then eluted with 0.1 N hydrochloric acid. This fraction was shown to contain radioactive ACTH and did not contain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1972
1972
1977
1977

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…The elevation of ACTH synthesis after adrenalectomy supports what others (12,15) have found by techniques of extraction and isolation of radioactively labeled rat ACTH by oxycellulose adsorption. Holub (6) also reported the suppression of ACTH synthesis by cortisone acetate.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The elevation of ACTH synthesis after adrenalectomy supports what others (12,15) have found by techniques of extraction and isolation of radioactively labeled rat ACTH by oxycellulose adsorption. Holub (6) also reported the suppression of ACTH synthesis by cortisone acetate.…”
Section: Discussionsupporting
confidence: 87%
“…These findings support the work of Wool et al (15), who used crude bovine ACTH as a marker corti cotropin for radioactively tagged ACTH, and Stackhouse et al (12), who reported rat ACTH by bioassay in their oxycellulose eluates. Neither of those reports examined this procedure as to its efficacy for extracting only rat pitu itary ACTH and particularly in terms of the starting material.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations